2020
DOI: 10.3389/fnins.2020.562830
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Subclinical Brain Alterations in Patients With Asymptomatic Carotid Vulnerable Plaques Using Intravoxel Incoherent Motion Imaging by Voxelwise Comparison: A Study of Whole-Brain Imaging Measures

Abstract: ObjectiveTo preliminarily explore subclinical brain alterations in an asymptomatic carotid vulnerable plaque group based on intravoxel incoherent motion (IVIM) imaging through voxelwise comparison in the whole brain.Materials and MethodsForty-nine elderly participants underwent multi-b-value DWI, of whom 24 participants with asymptomatic carotid vulnerable plaques and <50% stenosis served as the test group, while the rest served as the healthy control group. After fitting the double-exponential model, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although LDL is considered risky for cardiovascular disease and atherosclerosis, recent research indicated its potential protective role in neuroinflammation [84]. A Chinese study found low LDL levels might associate with microstructural brain damage [85], and a higher LDL/HDL ratio could impact T2DM patients' cognitive function by damaging functional connectivity [86]. Circulating ammonia, HDL or additional hepatic biomarkers failed to demonstrate significant mediation between NAFLD and cortical outcomes, potentially attributable to our "product of coefficients" and "delta" two-step approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although LDL is considered risky for cardiovascular disease and atherosclerosis, recent research indicated its potential protective role in neuroinflammation [84]. A Chinese study found low LDL levels might associate with microstructural brain damage [85], and a higher LDL/HDL ratio could impact T2DM patients' cognitive function by damaging functional connectivity [86]. Circulating ammonia, HDL or additional hepatic biomarkers failed to demonstrate significant mediation between NAFLD and cortical outcomes, potentially attributable to our "product of coefficients" and "delta" two-step approach.…”
Section: Discussionmentioning
confidence: 99%